The Personality Dimension Neuroticism, Extraversion, and Openness to experience that appears in the character in The Three button Trick and Other Stories by Nicola Barker - Rosmiati Rosmiati; Era Wahyu Ningsih; Siti Norhidayah (ELS Journal on Interdisciplinary Studies in Humanities, 2024)
This study examines the relationship between the characters' personalities and the three personality dimensions—Neuroticism, Extroversion, and Openness to Experience—in Nicola Barker's novel *The Three Button Trick and Other Stories*. The research aims to identify the types of violations committed by the characters and to explore the personality dimension relationships depicted through their personalities. The theoretical framework for this research includes Paul Grice's theory of maxim violation, which is used to explain personality relations, and the Five Factor Theory introduced by McCrae and Costa, which helps describe the personalities of the characters. A qualitative research method is employed to analyses the data, focusing on the maxim relations produced by the characters that reflect their personalities during communication. The data is collected from the text, sorted, analysed, and described according to the research needs. Triangulation is used to combine various data and sources for analysis. The results reveal that there are violations of maxim relations, habits, and personality exchange functions, demonstrating that personalities are interconnected. Ultimately, in the process of conversation, there can be a mutual understanding of the interlocutor's personality.